Optimasi perancangan mesin sablon cup dua warna semi otomatis - Riki Purnomo; Mafruddin Mafruddin; Sulis Dri Handono; Bambang Surono (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
In this modern era, the problem of packaging has become a part of everyday people's lives, especially in relation to food products. Cup drink MSME business actors have started using labels to market and create a special attraction for their products. At this time cup printing has begun to use machines, but the machines commonly used are only capable of printing one color and cannot print two or more colors and the price of the machines is still quite expensive. The purpose of this research is to optimize and redesign a one-color cup screen printing machine into a cup screen printing machine design that is practical and capable of printing two or more colors, to determine the power consumption of the electric motor on a two-color cup screen printing machine, and to determine the capacity and production yield of cup screen printing machines. two colours. The research method used was experimental by designing and manufacturing and testing a semi-automatic two-color screen printing device. Tests were carried out with variations in molding dimensions of 14 Oz and 16 Oz. From the results of the study it can be concluded that molding size has no effect on electric motor power, electricity consumption costs, production capacity, and screen printing quality. The dimensions of the semi-automatic two-color cup screen printing machine are 90 cm high, 60 cm wide, 30 cm thick, 374.5 watt electric motor power, electricity usage production costs Rp. 3.4 per cup, production capacity of 150 Cups/hour, and quality good screen printing reaches 92%.